2011
DOI: 10.1590/s1413-86702011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis as zoonosis: between proof of principle and paradigm in the Northwestern region of São Paulo State, Brazil

Abstract: Objective: In order to evaluate the potential zoonotic transmission of Giardia duodenalis, isolates from humans and dogs in the Northwestern region of the São Paulo State, Brazil were characterized based on the β-giardin gene. Methods: The samples were analyzed by sequencing of the Nested-PCR products. Results: The A1 and A2 subgenotypes were detected in human and dogs. Cysts of assemblage B, C and D have not been found in any isolates studied. Conclusions: These results are consistent with the view that giard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…47 Recently, in São José do Rio Preto, northwestern São Paulo State, all the detected isolates of G. intestinalis have been of the A genotype in humans and dogs (AI and AII subgenotype) showing the presence of zoonotic genotypes in the canine population of the region. 48 In this work in the city of Araçatuba, all the positive results were compatible with the AI genotype of G. intestinalis. Although the farm animal genotype of G. intestinalis (E) seems to be the commonest in cattle, studies in Canada and Australia have shown that a small proportion of cattle in a herd can be hosts of the A genotype, the most common human genotype.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…47 Recently, in São José do Rio Preto, northwestern São Paulo State, all the detected isolates of G. intestinalis have been of the A genotype in humans and dogs (AI and AII subgenotype) showing the presence of zoonotic genotypes in the canine population of the region. 48 In this work in the city of Araçatuba, all the positive results were compatible with the AI genotype of G. intestinalis. Although the farm animal genotype of G. intestinalis (E) seems to be the commonest in cattle, studies in Canada and Australia have shown that a small proportion of cattle in a herd can be hosts of the A genotype, the most common human genotype.…”
Section: Discussionsupporting
confidence: 66%
“…Hence, the frequency of transmission from dog to dog would be less frequent and acquired infections of zoonotic genotypes in dogs would also be more likely to persist. 51 Interestingly, the same genotypes were found in the municipalities of Araçatuba and São José do Rio Preto, 48 which have similar climatic characteristics and geographical locations as both are in the northwestern region of São Paulo State. The feces of most of the pets in this study were from a local animal shelter, and therefore, from strays and abandoned animals.…”
Section: Discussionmentioning
confidence: 62%
“…Similar A/B proportions have been previously reported in individuals of paediatric age in the State of Santa Catarina [69], in Amerindian children in the State of Amazonas [70], in deprived communities in the State of São Paulo [57], and in patients attending a hospital setting in Rio de Janeiro [71]. Interestingly, the presence of assemblage A, but not assemblage B, has been described in a few epidemiological surveys targeting clinical patients in the State of São Paulo [72], and paediatric populations [73] and people from disadvantaged communities seeking medical care [74] in Rio de Janeiro. In contrast, assemblage B was more prevalently found in asymptomatic children attending a day-care centre in the State of São Paulo [75].…”
Section: Discussionmentioning
confidence: 95%
“…Zoonotic genotypes A and/or B were reported in dogs, cats, non-human primates, cattle, sheep, exotic and wild animals in Brazil (Volotao et al 2007(Volotao et al , 2008(Volotao et al , 2011Souza et al 2007;Gomes et al 2011;Soares et al 2011;Paz e Silva et al 2012a,b;Fava et al 2013), suggesting the potential for environmental contamination and a risk for goat infection.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, studies on the molecular epidemiology of Giardia duodenalis are scarce, but the genotyping of isolates has been reported in dogs, cats, cows, sheep, non-human primates, and exotic and wild animals (Volotao et al 2007;Souza et al 2007;Volotao et al 2008;Volotao et al 2011, Gomes et al 2011Soares et al 2011;Paz e Silva et al 2012a; Paz e Silva et al 2012b;Fava et al 2013).…”
mentioning
confidence: 99%